Інновації як основа модернізації сучасного суспільства - Хаустова, М. Г. (НДІ ПЗІР НАПрН України, 2022)
У статті проаналізовано поняття модернізації правової системи, що являє собою еволюційну зміну синтезованої сукупності правових явищ і процесів, зумовлену міжнародними глобалізаційними процесами, з метою якісно нового впливу на правове життя суспільства, визначені її загальні ознаки. Визначено, що розбудова України як демократичної та правової держави неможлива без подальшого реформування національної правової системи. Аналізується участь зовнішніх партнерів у здійсненні модернізації та проведенні інноваційних процесів в Україні і підкреслюється, що найбільша роль з огляду на географічні чинники, безперечно, належить Європейському Союзу, який є найближчим до нас серед гравців, що мають високий потенціал впливу на глобальні процеси та сформовані на основі порядків відкритого доступу. Визначено, що головною метою державної інноваційної політики є створення соціально-економічних, організаційних і правових умов для ефективного відтворення, розвитку й використання науково-технічного потенціалу країни, забезпечення впровадження сучасних екологічно чистих, безпечних, енергота ресурсозберігаючих технологій, виробництва та реалізації нових видів конкурентоздатної продукції. Одним з ключових принципів вказаної політики є ефективне використання ринкових механізмів для сприяння інноваційній діяльності, підтримка підприємництва у науково-виробничій сфері. Обраний Україною шлях інтеграції до Євросоюзу вимагає зближення та інтеграцію національної економічної системи до систем країн ЄС. Це ставить Україну перед вибором запровадження тієї моделі розвитку, яка прийнята ЄС за базову, тобто моделі інноваційного розвитку. Особливими вимогами до характеру та темпів розвитку національної економіки стають завдання забезпечення її відтворювального інноваційного циклу на новій технологічній основі в умовах ринкової економіки, а також забезпечення соціальної спрямованості цього відтворювального циклу з максимально ефективним використанням інноваційного потенціалу країни, внутрішніх та зовнішніх ресурсів, досягнення випереджальних темпів динаміки розвитку порівняно з провідними країнами світу відповідно до напряму прогресу світової економіки. Таким чином, утвердження інноваційної моделі розвитку національної економіки забезпечить її конкурентоспроможність та вихід на траєкторію сталого розвитку. Тому перехід до інноваційної моделі розвитку національної економіки поступово стає імперативом державної політики. Problem setting. Current events in Ukraine have forced a new look at the concept of “modernization of the legal system” and innovation processes. The process of modernization of the legal system is developed on the initiative and with the support of the state and through legal means of influence on society. This process has long had a great impact on the nature and state of Ukrainian statehood, the role of law in our society, the understanding of law by Ukrainians, their attitude to law and the state. Analysis of resent researches and publications. The analysis of modernization and innovation processes in politics is conditioned by the need to study the problem of political transformations of the Ukrainian state and society, changes in the political system, transformation of political life, search for alternative ways out of crisis situations. Innovative political development takes place in the context of global transformations on a global scale. This means the need to study and apply foreign, international experience in the development and implementation of innovations in political practice, taking into account Ukrainian conditions. Modernization and innovation processes in public and political life are studied in the works of T. Parsons, S. Eisenstadt, D. Lerner, W. Moore, A. Etzioni, W. Rostow, G. Almond, S. Verb, L. Binder, L. Pai, S. Huntington, A. Toynbee, P. Sorokin, K. Jaspers, Palamarchuk M.O., Glibko S.V., Simpson O.E. and others. Target of research. The process of modernization and innovation are of great importance in the life of Ukraine. The idea of modernization and innovation can be considered as an idea that unites Ukraine, as part of the state ideology, as the dominant development of Ukraine. These ideas influenced further progress in economic, scientific, technical, social and other relations. Studying the peculiarities of the processes of modernization of law in Ukraine is not only interesting but also useful from a practical point of view. The concept of innovative modernization is studied, which changes the type of socio-economic development of society and requires the transformation of the existing political system. Article’s main body. Modernization as a global process entails changes, including in the social sphere. These include increasing social mobility and quality of life, forming institutions of social policy and civil society, increasing the value of human capital, the need for constant investment in professional development and staff development, improving education, expanding access to tangible and intangible benefits. Competition and constant development are the main prerequisites for modernization processes. Innovation should be understood as a commitment to think and act in a way that promotes continuous improvement by identifying, disseminating and embracing creative ideas. Innovation should improve public policy, administration and the re-use of existing knowledge, as well as the creation and application of new knowledge. In a broad sense, innovations are the latest data that are implemented regardless of the scope; it is usually a product of intellectual activity of the actors who implement them. Conclusions and prospects for the development. Thus, innovation is an innovation that radically transforms social reality. Today the country needs innovative modernization, which changes the socio-economic development of society and requires the transformation of the existing political system. Innovative modernization is a significant increase in the ability of the political system to stably and successfully adapt to new patterns of socio-political goals and create new types of relationships, institutions, practices based on innovation in economic, social, regional, international policy and other spheres of life.
Keywords: інноваційна політика; державна політика; правова система; глобалізація; трансформація; innovation policy; legal policy; legal system; transformation